Watershed Continuum Monitoring Approach: combining multiple water quality patterns along stream and river flowpaths to track sources, pathways, and processing of pollutants - Sujay S. Kaushal; Ashley E. Mon; Stanley B. Grant; Paul M. Mayer; Aaron J. Porter; Andrew J. Sekellick; Jason H. Chase; Shantanu V. Bhide; John D. Jastram; Tamara A. Newcomer-Johnson; Sydney A. Shelton; Alexis M. Yaculak; et al. (Ecological Engineering, 2026)

Determinants of Softwood Lumber Prices in the US Northwest - Jeffrey J Reimer; Kenneth Annan (Forest Science, 2023)
Lumber prices can be volatile and hard to predict from month to month yet are important for many sectors of the economy, ranging from forestry and construction. An economic model of lumber prices was developed and applied to data representing multiple supply and demand determinants of lumber. Using a suite of econometric models, monthly lumber prices were related back to variables including construction permits, US reserve bank credit, tariffs with Canada, exchange rates with Canada, and variables representing shocks associated with the COVID-19 pandemic. Preferred models use relatively small amounts of publicly available information, making them more accessible to industry participants who want to make their own price predictions. Such information can help guide decisions about whether to expand or scale back an operation in preparation for likely future price movements.

Arsenic speciation in the bracket fungus Fomitopsis betulina from contaminated and pristine sites - Mark Button; Iris Koch; Michael J. Watts; Kenneth J. Reimer (Environmental Geochemistry and Health, 2020)

Arsenic Speciation, Distribution, and Bioaccessibility in Shrews and Their Food - Maeve M. Moriarty; Iris Koch; Kenneth J. Reimer (Archives of Environmental Contamination and Toxicology, 2012)